Actions strategic preventive intervention in socio-educational matters to address the school bullying from the draft Law on Peaceful School Coexistence (Revista Electrónica REDINE, 2024)
This essay, as a result of a documentary review, proposes eighteen (18) actions strategic preventive intervention in socio-educational matters to address the school bullying from the Draft Law on Peaceful School Coexistence, this with the purpose to timely manage situations that degrade human and moral integrity. This means unifying multifactorial efforts that result in the construction of a positive school climate, interpersonal relationships and coherent performance of pedagogical action. It is concluded that the preventive intervention of bullying must begin with positive psychosocial care that favors the social, affective and emotional throughout the life cycle, as well as the full development of their personality.
Keywords: humans rights; socio-educational coexistence; moral integrity; psychological well-being; functional performance